The Optimization Problem for Finding the Stress State of a Composite Body - K.S. Mamedova (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2014)
The method criterion and a method of the decision of a problem of the theory of elasticity on decrease in concentration of pressure in a compound body by optimization of the form of border of connection of various environments is given.